IDENTIFIKASI KETERAMPILAN PROSES SAINS MELALUI PENERAPAN LEARNING CYCLE 5E PADA SISWA MA NW LENEK LAUQ - Zohratul Aini; Muhammad Zulhariadi; Nening Listari (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2019)
This study aims to identify the science process skills (KPS) through the application of the 5E Learning Cycle in students of Islamic Senior High School (MA) NW Lenek Lauq. The type of research is a quase experiment with the Nonequivalent Control Group Design. The population in this study were all MA NW Lenek Lauq students. The sample of this study was class X IPA-1 and X IPA-2 which were taken using purposive sampling technique. Class X IPA-1 numbered 27 people as an experimental class treated with the Learning Cycle 5E model and class X IPA 2 numbered 23 people as a control class treated with the conventional model. The research instrument used was a science process skills test, a KPS test in the form of pre-test and post-test and observation sheet of the implementation of learning. Data analysis in this study used the t-test to determine the effect of the 5E learning cycle on science process skills. The results obtained an average value of the experimental class 51.41 (pre-test) to 82.52 (post-test), while the control class from 49.74 (pre-test) to 65.22 (post-test). Based on the results of the analysis of the hypothesis test with the t-test obtained a significance value of 0.000, which is smaller than 0.05 (0.000 <0.05), which is that there is a significant effect of the Learning Cycle 5E model on KPS (H0 rejected). The conclusion from the results of this study is that there is an influence of the 5E learning cycle model on students' science process skills (KPS).